THE ROLE OF TELEMEDICINE IN THE DIAGNOSIS OF PATIENTS WITH COMBINED INJURIES OF THE MAXILLOFACIAL SKELETON - Bakiyeva SH.X.; Karimberdiyev B.I; Djurayev J.A (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Combined injuries of the maxillofacial skeleton require rapid and accurate diagnosis to ensure timely treatment and prevent complications. In recent years, telemedicine has become an important tool in trauma diagnostics, enabling remote consultation, image sharing, and specialist involvement. This study evaluates the role of telemedicine in the diagnostic process of patients with combined maxillofacial injuries. A total of 140 patients were analyzed using clinical examination, radiological imaging, and telemedicine-based consultation systems. The results demonstrated that telemedicine significantly improves diagnostic accessibility, reduces time to diagnosis, and enhances the accuracy of clinical decision-making. The study confirms that telemedicine is an effective supplementary tool in the management of maxillofacial trauma, especially in emergency and remote healthcare settings.